Does knowledge matter for the environment? Global evidence of economic complexity and ecological footprints - Nguyen, Canh Phuc (Archīum Ateneo, 2022)
This study endeavors to explore the impact of knowledge materialized in production on the environment by examining the influences of economic complexity on ecological footprints. The empirical analysis is carried out for a global sample of 95 economies comprising 30 low- and lower-middle-income economies, 27 upper-middle-income economies, and 38 high-income economies. The robust results from several panel estimates show two interesting findings. First, the economic complexity has an inverted U-shaped relationship with the ecological footprints of production and consumption in the full sample. Second, that relationship is confirmed in lower-middle-income, but not in upper-middle-income economies. Moreover, the inverted U shape is evidenced by the Consumption Ecological Footprint in high-income economies. The results imply the existence of an Economic complexity Ecological Kuznets Curve in the relationship between economic complexity and ecological footprints.